2020
DOI: 10.1016/j.molp.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The RALF1–FERONIA Complex Phosphorylates eIF4E1 to Promote Protein Synthesis and Polar Root Hair Growth

Abstract: The molecular links between extracellular signals and the regulation of localized protein synthesis in plant cells are poorly understood. Here, we show that in Arabidopsis thaliana, the extracellular peptide RALF1 and its receptor, the FERONIA receptor kinase, promote root hair (RH) tip growth by modulating protein synthesis. We found that RALF1 promotes FERONIA-mediated phosphorylation of eIF4E1, a eukaryotic translation initiation factor that plays a crucial role in the control of mRNA translation rate. Phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
139
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 73 publications
(140 reference statements)
2
139
0
Order By: Relevance
“…Exactly how the dose-dependency phenotypes are mediated by FER-K565R-GFP needs further research. Recently, Zhu et al 2020 noticed that FER-K565R/fer-4 is still able to partially phosphorylate one of the FER kinase substrates (eukaryotic initiation factor 4E 1; elF4E1) to promote root hair growth in response to RALF1 peptides (Zhu et al 2020). This indicates that FER's ability to phosphorylate its substrate can be partially masked by FER-K565R ''kinase-dead'' mutants via an as-yet unknown mechanism.…”
Section: Is Fer Kinase Activity Essential For Its Function?mentioning
confidence: 99%
See 4 more Smart Citations
“…Exactly how the dose-dependency phenotypes are mediated by FER-K565R-GFP needs further research. Recently, Zhu et al 2020 noticed that FER-K565R/fer-4 is still able to partially phosphorylate one of the FER kinase substrates (eukaryotic initiation factor 4E 1; elF4E1) to promote root hair growth in response to RALF1 peptides (Zhu et al 2020). This indicates that FER's ability to phosphorylate its substrate can be partially masked by FER-K565R ''kinase-dead'' mutants via an as-yet unknown mechanism.…”
Section: Is Fer Kinase Activity Essential For Its Function?mentioning
confidence: 99%
“…Chen et al 2016 found that only the fulllength FER kinase domain interacted with ABA Insensitive 2 (ABI2), but that each of the two halves showed no interaction when assessed using the yeast two-hybrid system; FER-K565R also reduced the interaction with ABI2 in vitro, suggesting FER kinase activity may be important for the FER-ABI2 interaction (Chen et al 2016) FER can also directly interact with and phosphorylate ErbB3-binding protein 1 (EBP1), and the FER cytoplasmic domain (FER-CD) and FER-CD K565R all physically associate with EBP1 in GST pull-down assays, suggesting that FER kinase activity may not be necessary for the FER-EBP1 interaction but that it may be necessary for RALF1-induced phosphorylation of EBP1 . Zhu et al 2020 found the interaction of FER and its substrate eIF4E1 is regulated by their reciprocal phosphorylation (Zhu et al 2020). Together, these results indicated that FER kinase activity may not be necessary for control of PT reception, but it may be necessary for the RALF1 response in root growth.…”
Section: Is Fer Kinase Activity Essential For Its Function?mentioning
confidence: 99%
See 3 more Smart Citations